2005
DOI: 10.1159/000081746
|View full text |Cite
|
Sign up to set email alerts
|

Virological and Biochemical Relapse after Discontinuation of Lamivudine Monotherapy for Chronic Hepatitis B in Japan: Comparison with Breakthrough Hepatitis during Long-Term Treatment

Abstract: Objective: Comparison of virological and biochemical relapse in patients with chronic hepatitis B, based on continuation or discontinuation of lamivudine monotherapy. Methods: In Japanese genotype C-dominant hepatitis B patients, 25 patients who stopped treatment at normal levels of alanine transferase (ALT) were retrospectively compared with 75 patients who continued treatment. Both groups were matched for age, sex, and observation period after start of treatment. We investigated the relapse rates, and evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 100 publications
1
9
1
Order By: Relevance
“…Recently, cessation of antiviral agent discussed in the previous studies [12,13,19,20], but biochemical breakthrough, hepatitis flare, and retreatment outcome were not closely investigated, especially in HBeAg-negative patients. Post-treatment virologic relapse and biochemical breakthrough incidence rates in our study were low in patients who achieved undetectable serum HBV DNA level and were lower than those of previous studies [12,13,21-24]. Moreover, patients in our cohort were regularly and closely followed up after cessation of lamivudine.…”
Section: Discussioncontrasting
confidence: 64%
“…Recently, cessation of antiviral agent discussed in the previous studies [12,13,19,20], but biochemical breakthrough, hepatitis flare, and retreatment outcome were not closely investigated, especially in HBeAg-negative patients. Post-treatment virologic relapse and biochemical breakthrough incidence rates in our study were low in patients who achieved undetectable serum HBV DNA level and were lower than those of previous studies [12,13,21-24]. Moreover, patients in our cohort were regularly and closely followed up after cessation of lamivudine.…”
Section: Discussioncontrasting
confidence: 64%
“…Hence, our results indicate that longterm lamivudine treatment also induces long-term favorable prognosis and is safe in patients with breakthrough hepatitis if suitable additional treatments are provided, to say nothing of the favorable prognosis in patients without YMDD mutant and breakthrough hepatitis. We agree with Lok et al [2003] who provided data in support of the benefits of long-term lamivudine treatment [Akuta et al, 2004].…”
Section: Discussionsupporting
confidence: 51%
“…It was reported that the defective replicative competency of p.M204V/I restores upon addition of lamivudine, and there is no benefit to continue lamivudine therapy after emergence of YMDD mutations. 15,16 Pyrosequencing in our experiments (Table 4) showed a high accuracy in quantifying the proportions of MUT/(MUT+WT) to identify artificially made samples with minor mutations, predominatedly mutant, and equal mixtures. Lee and colleagues demonstrated that YMDD mutations occur throughout the course of lamivudine therapy, and a 5-fold predominance of YMDD mutant to WT virus is significantly associated with viral DNA breakthrough, 17 the ability of pyrosequencing to finely quantify the proportions of MUT/(MUT+WT) may be helpful for prediction of viral DNA breakthrough.…”
Section: Discussionmentioning
confidence: 74%